Characterization of Hepatitis C Virus IRES Quasispecies – From the Individual to the Pool - Vopálenský, Václav; Khawaja, Anas; Rožnovský, Luděk; Mrázek, Jakub; Mašek, Tomáš; Pospíšek, Martin (Frontiers in Microbiology, 2018)
Hepatitis C Virus is a single stranded positive-sense RNA virus from the genus Hepacivirus. The viral genomic +RNA is 9.6 kb long, contains highly structured 5' and 3' untranslated regions and codes for a single large polyprotein, which is co- and post-translationally processed by viral and cellular proteases into at least 11 different polypeptides. Most of the 5′ untranslated region and an initial part of the polyprotein gene are occupied by an internal ribosome entry site (IRES), which mediates cap-independent translation of the viral proteins and allows the virus to overcome cellular antiviral defense based on the overall reduction of the cap-dependent translation initiation. We reconsidered published results concerning a search for possible correlation between patient response to interferon-based antiviral therapy and accumulation of nucleotide changes within the HCV IRES. However, we were unable to identify any such correlation. Rather than searching for individual mutations, we suggest to focus on determination of individual and collective activities of the HCV IRESs found in patient specimens. We developed a combined, fast and undemanding approach based on high-throughput cloning of the HCV IRES species to a bicistronic plasmid followed by determination of the HCV IRES activity by flow cytometry. This approach can be adjusted for measurement of the individual HCV IRES activity and for estimation of the aggregate ability of the whole hepatitis C virus population present in the specimen to synthesize viral proteins. To detect nucleotide variations in the individual IRESs, we used denaturing gradient gel electrophoresis (DGGE) analysis that greatly improved identification and classification of HCV IRES variants in the sample. We suggest that determination of the collective activity of the majority of HCV IRES variants present in one patient specimen in a given time represents possible functional relations among variant sequences within the complex population of viral quasispecies better than bare information about their nucleotide sequences. Similar approach might be used for monitoring of sequence variations in quasispecies populations of other RNA viruses in all cases when changes in primary sequence represent changes in measurable and easily quantifiable phenotypes.